The introduction of playing cards and card playing in Russia - Shevtsov, Vyacheslav V. (Canadian-American Slavic studies)
This article examines when and how playing cards were introduced in Russia and links the adoption of card playing in the Russian Empire to the process of Westernization in the eighteenth and nineteenth centuries. The author examines the role of card playing in noble culture and in the context of wider historical problems: the transition from medieval to modern culture; the translation and perception of cultural novelties; and the relationship cards and card playing had with other forms of celebration and leisure. The article is based on various sources, including Russian laws, import-export (customs) records, private sources in noble family archives, and literary works.